Emerging technology trends in regulatory approvals of cancer immunotherapy drugs by the FDA and EMA - Maryam Monajati; Alimohammad Tamaddon; Samira Sadat Abolmaali (Shiraz University of Medical Sciences, 2024)
Immunotherapy is an emerging field in medicine using the body's immune to combat various diseases, particularly cancer. In recent years, several immunotherapy agents have obtained regulatory approval from the European Medicines Agency (EMA) and the U.S. Food and Drug Administration (FDA) for the management of different types of neoplasms. Notable developments include approvals for bispecific antibodies, antibody-drug conjugates, checkpoint inhibitors, and CAR T-cell therapies. They work by stimulating the immune system, suppressing the pathways that support cancer cells in evading immune system detection, or introducing genetically engineered immune cells to target specific antigens on cancer cells. These agents have demonstrated remarkable safety and efficacy in various clinical trials, targeting different mechanisms of action, indications, and patient populations. This article presents a thorough overview of the recent immunotherapy approvals granted by the FDA and the EMA, highlighting their mechanisms of action, indications, and clinical evidence. Overall, the recent approvals constitute a remarkable achievement in the advancement of novel and efficacious cancer therapies that can enhance patient outcomes and quality of life.